Spores of Serpocaulon (Polypodiaceae): morphometric and phylogenetic analyses. Issue 3 (4th May 2017) - Ramírez-Valencia, Valentina; Sanín, David
Abstract: The morphometry and sculpture pattern of Serpocaulon spores was studied in a phylogenetic context. The species studied were those used in a published phylogenetic analysis based on chloroplast DNA regions. Four additional Polypodiaceae species were examined for comparative purposes. We used scanning electron microscopy to image 580 specimens of spores from 29 species of the 48 recognised taxa. Four discrete and ten continuous characters were scored for each species and optimised on to the previously published molecular tree. Canonical correspondence analysis (CCA) showed that verrucae width/verrucae length and verrucae width/spore length index and outline were the most important morphological characters. The first two axes explain, respectively, 56.3% and 20.5% of the total variance. Regular depressed and irregular prominent verrucae were present in derived species. However, the morphology does not support any molecular clades. According to our analyses, the evolutionary pathway of the ornamentation of the spores is represented by depressed irregularly verrucae to folded perispore to depressed regular verrucae to irregularly prominent verrucae.